199k views
4 votes
Please HELP ME!!!!!! No one is helping me :(

Please HELP ME!!!!!! No one is helping me :(-example-1

1 Answer

2 votes
Obviously, you're solving for e. Divide both sides by 9f to get
e^(2)= (49)/(9f). Undo the square on the e by taking the square root of both sides, leaving you with
e= ( √(49) )/( √(9f) ). Both 49 and 9 are perfect squares, so simplify accordingly to get that
e=+/- (7)/(3 √(f) ). If you have to rationalize the denomiator, then your final answer would be
e=+/- (7 √(f) )/(3f)
User Greg Ostry
by
4.9k points